The Combined Effect of Haplodiplonty and Partial Clonality on Genotypic and Genetic Diversity in a Finite Mutating Population. (12th March 2021) - Stoeckel, Solenn; Arnaud-Haond, Sophie; Krueger-Hadfield, Stacy A
Abstract: Partial clonality is known to affect the genetic composition and evolutionary trajectory of diplontic (single, free-living diploid stage) populations. However, many partially clonal eukaryotes exhibit life cycles in which somatic development occurs in both haploid and diploid individuals (haplodiplontic life cycles). Here, we studied how haplodiplontic life cycles and partial clonality structurally constrain, as immutable parameters, the reshuffling of genetic diversity and its dynamics in populations over generations. We assessed the distribution of common population genetic indices at different proportions of haploids, rates of clonality, mutation rates, and sampling efforts. Our results showed that haplodiplontic life cycles alone in finite populations affect effective population sizes and the ranges of distributions of population genetic indices. With nonoverlapping generations, haplodiplonty allowed the evolution of 2 temporal genetic pools that may diverge in sympatry due to genetic drift under full sexuality and clonality. Partial clonality in these life cycles acted as a homogenizing force between those 2 pools. Moreover, the combined effects of proportion of haploids, rate of clonality, and the relative strength of mutation versus genetic drift impacts the distributions of population genetics indices, rendering it difficult to transpose and use knowledge accumulated from diplontic or haplontic species. Finally, we conclude by providing recommendations for sampling and analyzing the population genetics of partially clonal haplodiplontic taxa.